MITIGASI BENCANA BANJIR: KEGIATAN KELOMPOK KKN UNRAM DI DESA BANGKET PARAK, LOMBOK TENGAH - Ramadhan, Aldio Rivan; Silva, Kania; Akbar, Muhammad Maulana; Putri, Devi Febrianti; Tifriyadi, Tegar; Dwiani, Ni Nengah Anggi; Putra, Ade Irdiansyah; Aprilianti, Yeni; Jannah, Siti Raudhatul; Marhamah, Siti Nur (Jurnal Wicara, 2023)
Bangket Parak Village is a village located in Pujut District, Central Lombok Regency. This village is a division of Teruwai Village in 2010. In this village floods often occur every year which have an impact on losses for the community. This flood was caused by a fairly high intensity of rain accompanied by overflowing river water and water shipments from upstream. Therefore, the DESTANA (Disaster Response Village) Program is here to assist in solving these problems. Some of the efforts made to deal with flooding in Bangket Parak Village include: 1) Conducting socialization related to disaster mitigation; 2) Installation of natural disaster signs; and 3) Manufacturing and installation of EWS (Early Warning System).